Configuring the digital farmer: A nudge world in the making? - Brooks, Sally (Economy and society, 2021)
This paper explores the 'digital farmer' assemblage as an illuminating case of the behavioural turn in international development, in which smallholder farmers are digitally steered towards behaviours deemed necessary for market inclusion. Central to these interventions are digital platforms that function as human technologies to craft new kinds of market subject that can be inserted into value chains and wider circuits of capital and data. As such, they represent both a continuation of the 'long' Green Revolution and a point of departure. The narrowing of options built into their design is likely to further erode processes of skilling central to agricultural practice, while loosening the social ties of mutuality and reciprocity in which such processes are embedded, intensifying vulnerability to climate and market uncertainties.